PEMANFAATAN LIMBAH RUMAH TANGGA SEBAGAI PAKAN TERNAK DALAM UPAYA PENGUATAN EKONOMI DI KELURAHAN GUNUNG LINGAI - Erni Setiawati; Mutiara Rahman; Ni Nyoman Ayu Fenika (Wadah Inovasi Indonesia, 2022)
Organic waste from home can be managed and used to make animal feed ingredients. Black soldier flies, also known as maggots, can be used as a substitute or addition to industrially processed feeds. Maggots are organisms that originate from the eggs of the black soldier fly. It is one of those organisms that decay because they grow by eating organic matter. This PKM hopes that the residents of Jalan Gunung Lingai have sufficient knowledge and expertise in utilizing household waste and cultivating animal feed (maggot) as a substitute for factory processed feed, thus increasing residents' income from maggot cultivation entrepreneurial activities.